NYANYIAN LIRIS: NYANYIAN RAKYAT MINANGKABAU (Lyrical Song, Minangkabau Folk Song) - Eva Krisna; Krisnawati Krisnawati (Salingka, 2015)
AbstractThis writing aimed to document the lyrical folk songs of Minangkabau and to investigate the functions contained in the songs anthropologically. Thus, this writing used the anthropological approach and the functions theory. Of all the kinds of folk songs, such as functional song, lyrical song, and narrative song, Minangkabau ethnic group owns lyrical song with many kinds of genre that still can be traced until now. This kind of folk songs relatively belongs to all sub-ethnic group (nagari) of Minangkabau. Some of the titles of the songs are “Kamang Bakayu” (The Kamang people collect firewood), “Bukik Apik Marandang Kopi” (The Bukit Apit people simmer coffee), “Solok Manuai” (The Solok people harvest rice), “Cupak Maambiak lado” (The Cupak people harvest chili), and “Guguak Manitik Ameh” (The Guguk people inlay jewel on gold). These song titles shows the sub-ethnic group or the region of living of every community in Minangkabau, also the occupation of the people have. The folk songs are tended to be extinct due to the active heirs are in old ages and the inheritance process is no longer happened, whereas the songs contains of functions that have benefits for their supporters. The functions themselves caused the popularity of the songs in the past.Keywords: folk songs, Minangkabau lyrical song, anthropological approach, and functions theoryAbstrakTulisan ini bertujuan mendokumentasikan nyanyian liris rakyat Minangkabau dan mengkaji fungsifungsi yang terkandung di dalamnya dalam kerangka antropologi. Dengan demikian, tulisan ini menggunakan pendekatan antropologis dan teori fungsi. Di antara jenis-jenis nyanyian rakyat, seperti Nyanyian Berfungsi, Nyanyian Liris, dan Nyanyian Kisahan, suku bangsa Minangkabau memiliki jenis Nyanyian Liris dengan berbagai ragam yang masih dapat ditelusuri hingga saat ini. Ragam nyanyian rakyat dimaksud relatif dimiliki oleh semua subsuku bangsa (nagari) di Minangkabau. Beberapa judul nyanyian tersebut di antaranya adalah “Kamang Bakayu” (Orang Kamang mengumpulkan kayu bakar), “Bukik Apik Marandang Kopi” (Orang Bukit Apit merendang kopi), “Solok Manuai” (Orang Solok menuai padi), “Cupak Maambiak Lado” (Orang Cupak memanen cabe), dan “Guguak Manitik Ameh” (Orang Guguk menatah/memasang permata pada emas). Juduljudul tersebut menunjukkan subsuku bangsa atau nagari tempat berdiam setiap kelompok masyarakat di Minangkabau serta mata pencaharian (jenis pekerjaan) yang mereka tekuni. Nyanyian rakyat tersebut dikhawatirkan akan punah karena pewaris aktifnya saat ini telah berusia lanjut dan proses pewarisan tidak berlangsung lagi. Padahal, nyanyian rakyat tersebut mengandung fungsi-fungsi yang sangat bermanfaat bagi khalayak pendukungnya. Fungsi-fungsi itulah yang menyebabkan nyanyian rakyat tersebut disukai dan popular pada suatu ketika di masa lalu.Kata Kunci: nyanyian rakyat, nyanyian liris Minangkabau, pendekatan antropologis, dan teori fungsi